Management of Sub-gingival Fracture of Tooth by Multi-disciplinary Approach - Khan, Atiquzzaman; Chowdhury, Shirin Sultana; Ahmed, Rubaba; Rahman, Mirza Md Arifur; Quader, SMA (International Journal of Human and Health Sciences (IJHHS), 2019)
Dental trauma is commonly occur in children and may involve adult person also. In permanent dentition crown fracture is common and it may be uncomplicated or complicated. Complicated crown-root fractures require a multidisciplinary treatment modality for longterm success. Here we presented multidisciplinary treatment of a traumatized permanent maxillary incisor of a young male patient where oblique tooth fracture involved coronal pulp. As more than 50% of the crown and palatal coronal part of the root had been fractured and the tooth could not be properly isolated during endodontic procedure which is essential for success of root canal treatment. An intra-canal wire hook was cemented in the root canal and attached to another wire fixed to the adjacent teeth. With the help of elastic band attached with hook the fractured tooth fragment was extruded to create clinical crown. Finally, gingival re-contouring was performed to establish optimum biological width. At last, porcelain fused to metal crown was placed and the patient was comfortable both esthetically and functionally. International Journal of Human and Health Sciences Vol. 03 No. 03 July’19. Page: 165-168